Indoctrinating Limited Liabilty in Partnership Business Entities: The Development in Malaysia - Abd Ghadas, Prof. Dr. Zuhairah Ariff (SWEET & MAXWELL, 2018)
Prior to the millennium era, there was only one partnership business entity in Malaysia, namely the general partnership which was governed by the Partnerships Act 1961. In 2012, a new business entity, known as Limited Liability Partnerships was introduced in Malaysia. The Limited Liability Partnership Act 2012 (LLP Act) was passed and gazetted in February 2012. The LLP Act 2012 is the outcome of an initiative by the Companies Commission of Malaysia to develop the local market. It marked a major development in Malaysian business laws after more than half a century of independence. This new business entity allows general traders and a few professionals such as lawyers and accountants to set up an incorporated business entity which is not a company. The Malaysian LLP is a hybrid business entity which enjoys both partnership and corporate attributes. Although the LLP has the status of a body corporate, its internal regulation is similar to a partnership. One of the significant developments of law which the LLP enriched is altering the unlimited liability regime in partnership based business entities. This article discusses and highlights the development and application of limited liability in Malaysia’s partnership based entities.